Arctic Maintenance Considerations. - ARMY TEST AND EVALUATION COMMAND ABERDEEN PROVING GROUND MD (1972)
The report provides background information on the test of materials in an arctic environment. It describes arctic environmental characteristics and the effects of cold weather on solid materials, personnel, and maintenance. It discusses personnel saftey, maintenance equipment, and the maintenance of material such as vehicles, aircraft, weapons, small arms, muntions, electrical equipment, optical equipment, personnel clothing and equipment to include design considerations. (Author)